Meleagrin from marine fungus Emericella dentata Nq45: crystal structure and diverse biological activity studies. Issue 21 (2nd November 2021) - Hamed, Abdelaaty; Abdel-Razek, Ahmed S.; Araby, Mariam; Abu-Elghait, Mohammed; El-Hosari, Doaa G.; Frese, Marcel; Soliman, Hesham S. M.; Stammler, Hans Georg; Sewald, Norbert; Shaaban, Mohamed
Abstract: The crystal structure and unambiguous absolute configuration of meleagrin (1 ) isolated from fungus Emericella dentata Nq45 is reported herein to first time on the bases of single crystal X-ray diffraction. Together with 1, haenamindole (2 ), isorugulosuvine (3 ), secalonic acid D (4 ), ergosterol (5 ) and cerebroside A (6 ) were obtained and their structures were determined by ESI MS and NMR data analysis. Diverse biological activity of meleagrin (1 ) was investigated. Compound 1 pronounced potent cytotoxicity against the human cervix carcinoma cell line KB-3-1 and its multidrug resistant sub-clone KB-V1 of IC50 3.07 and 6.07 µM, respectively, in comparison with the reference (+) – griseofulvin (IC50 19, 19.5 µM). Based on the antibiofilm activity, compound 1 displayed as well potent activity against Staphylococcus aureus with an MIC of 0.25 mg/mL. Isolation of the producing fungus and taxonomical characterization is stated as well. Graphical Abstract: